Motivasi dan tantangan di awal yang sederhana: Kasus calon petinju muda Filipina (Batang Pinoy) - Pocaan, Jordan Miranda; Pasano, Analiza (Universitas Nusantara PGRI Kediri, 2022)
Many successful professional athletes start from a humble beginning where investing time, dedication, and hard work is required. This research investigates the motivations and challenges young Filipino (Batang Pinoy) athletes experience while pursuing careers in boxing. It purposively selected 10 young male boxing athletes who had already competed in provincial, regional and national games from the Bicol region, Philippines. Using a phenomenological approach, the participants participated in an in-depth interview using the validated interview questions. It reveals that poverty is portrayed as a great motivator of young athletes, where the life stories of successful world boxing champions serve as their basis. They are also influenced and supported by their peers and family in their boxing careers. However, insufficient facilities and fundings are mainly the cause of their struggles. This study serves as a call for the national governing body of sports in the country to further extend its efforts to support the needs of young potential athletes. Specifically, safety equipment and training, strengthening sports policies, and funding are necessary to solve these challenges.